The Constitutional Rights of Children Born Wedlock As Legal Subjects - Standy Wico; Rachmi Sulistyarini; Satria Amiputra Amimakmur (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines legal subjects, focusing on illegitimate children as legal subjects in the Indonesian legal system. Legal subjects include individuals or legal entities with legally recognized rights and obligations. In this context, children, as human beings, are legal subjects with basic rights guaranteed by the 1945 Constitution and related laws and regulations, including the Child Protection Law and the Marriage Law. Illegitimate children, born from unregistered marriages, often face challenges in legal recognition and the fulfillment of their rights. However, Indonesian law emphasizes that parents' marital status should not be a basis for discrimination against children, so that illegitimate children still have the right to legal recognition, identity, protection, and access to social, economic, and educational rights. This study emphasizes the importance of the principles of justice and legal certainty in providing protection for all legal subjects, including illegitimate children, to ensure their rights are fulfilled fairly and equitably. Thus, legal recognition of illegitimate children not only reflects compliance with national and international legal provisions but also supports the creation of social justice and child welfare. This research is expected to form the basis for a deeper understanding of the role of law in protecting children's rights as legal subjects without discrimination, as well as providing recommendations for more inclusive legal practices and policies.